Pemberdayaan Masyarakat melalui Sosialisasi Bank Sampah dalam Mendukung Pengelolaan Sampah Berkelanjutan di Desa Penggarutan: Community Empowerment through Waste Bank Socialization in Support of Sustainable Waste Management in Penggarutan Village - Nafila Azqia Zahra; Yassar Apriarahma; Evrizal Rizqy Ramadhan; Fauzan Ridho; Fajar Wahyu Samudra; Fauzan Putra Pratama; Nida Atika Sari; Azkia Rizki Ramadhanti; Sarah Zinta Tantiya Jasmine; Nadila Criswara; Reva Amelia Dewi; Syifa Ulkhayati; Ikhsan Pratama; Syaukaty Yasinta (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Waste management remains a major concern in various countries, including Indonesia. Improperly managed waste can negatively impact not only the environment but also the community's health, economy, and social well-being. Therefore, more effective and sustainable waste management is essential. The activities carried out included optimizing waste bank management through community outreach. The stages in implementing these activities include preparation, implementation, and monitoring and evaluation. The preparation phase aimed to identify the problems faced by residents of Penggarutan Village regarding the rampant unprocessed organic and non-organic waste. Offline activities were conducted, with the first stage being the registration of new customers. Prospective customers must register as waste bank customers before proceeding to the deposit stage. Deposits occur when waste is stored at the waste bank. Meanwhile, online waste bank operations are conducted through a web system, thereby minimizing errors in data recording, data loss, and damage to the paper used for recording. The outreach activities included explaining the waste bank system and the supporting waste bank website. Through these outreach activities, the community was equipped with the skills to separate organic and non-organic waste. By sorting and creating economic opportunities for the community, it is hoped that this waste bank will continue to operate as a way to reduce waste, a major problem. This program also represents a first step.